Genotype and Sowing Date Effects on Seed Yield of Olitorius Jute in Late Season (Bangladesh Agronomy Journal, 2020)
Feld experiments were conducted at four locations of Bangladesh (Manikgonj, Cumilla, Dinajpur and Joshore) to optimize sowing date for higher seed yield of jute in late sown condition. The experimental variables constituted with three genotypes (O-72, O-3820 and Acc.4311) and three sowing dates (31 July, 15 August and 30 August).Each experiment was laid out in a randomized complete block design with three replications. The treatment combinations were assigned randomly and afresh randomization was followed in each replication. Results showed that the genotype Acc.4311, O-72 and O- 3820 produced maximum number of branches (5.40, 4.90 and 4.40, respectively) plant-1 on 15 August sowing at Manikgonj. The genotype Acc.4311 produced higher number of pods plant-1 than other two genotypes (O-72 and O-3820) in all sowing dates andat all the locations. The highest number of seedspod-1 (220.80) was found from the genotype Acc.4311grown at Manikgonj which was statistically similar (196.90) with that of the same genotype sown on the same date at Joshore. The highest thousand seed weight (2.478 g) was recorded from the seeds of genotype Acc.4311 sown on 15 August at Manikgonj followed by same genotype at Joshore.Finally, the genotype Acc.4311 sown on 15 August produced the highest seed yield (2.478 t ha-1) at Manikgonjwhich was significantly higher than those of sown on 31 July and 30 August at the same location. As the genotype Acc.4311 was found outstanding sown on 15 August over locations, this genotype may be considered promising for higher seed yield of olitorius jute in late season.Bangladesh Agron. J. 2019, 22(2): 83-89